Implementasi dan Efektivitas Program Kampung Zero Waste di Kelurahan Tambaksari RW 01 - Anggie Devitasari; Raden Kokoh (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Many large cities in Indonesia, including Surabaya, face major problems with urban waste management. One way to reduce the amount of waste generated is through the Zero Waste Village programme. This programme is an initiative of the city government of Surabaya with the aim of reducing waste and raising public awareness about waste management. The methods used are observation and interviews. The results of the implementation showed a decrease in the amount of waste in two regions. The success is supported by the active participation of the citizens. However, obstacles were also identified in the management of organic waste and in the extensive territorial and infrastructural constraints that support the programme's activities.